One-pot Three-component Synthesis of New Pyridine-fused Pyranoquinoline Derivatives - Ramadas, TMMV; Sri, Tunki Sowmya; Ugale, Vinod; Aravind, Seema; Reddy, Pedavenkatagari Narayana (Letters in Organic Chemistry, 2025)
A new series of pyridine-fused pyranoquinoline derivatives have been synthesized via one-pot three-component coupling of hydroxyquinoline, aromatic aldehydes, and 2-aminopropene-1,1,3-tricarbonitrile in the presence of 10 mol% of triethylamine at 80°C in ethanol under reflux conditions. It is an effective synthetic method due to its simple operating procedure, wide range of substrates, column chromatography-free separations, and high product yield.
Keywords: 4-hydroxy-1-methylquinolin-2(1H)-one